(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The small and enigmatic family Phenacoleachiidae is of phylogenetic interest due to its combination of derived and ancestral features and its very restricted Qistribution in the southem hemisphere. Previous studies have placed it with the archaeococcoids (Margarodidae sensu lato and Ortheziidae) or near the mealybugs (Pseudococcidae). This study re-describes and illustrates the first-instar nymph of Phenacoleachia zealandica (Maskell) and re-considers the relationships of Phenacoleachia as indicated by morphology and molecular data. Phylogenetic analysis of nuclear small-subunit ribosomal DNA suggests that Phenacoleachia is not closely related to the Pseudococcidae. The features that Phenacoleachia shares uniquely with Pseudococcidae either may be plesiomorphies that have been lost in more derived groups or may be convergent structures.